Some reasons associated with university desertion at the undergraduate level: The case of the School of Libraries, Documentation and Information, National University of Costa Rica - Canales García, Alba Luz (2007)
The student desertion is a topic of current importance, which, in spite of its importance for the educational system - specially, because it affects different areas of the national and personal development, for example: economic, social, moral, emotional and professional - has been studied fundamentally under a quantitative approach.The ignorance of the reasons that has the student body in Bibliotecology’ s School, Documentation and Information, of the National University, in Costa Rica; to abandon classrooms, it represents an obstacle in order to detain the increase in the quantity of desertions, which results are a gap difficult to level between graduated and undergraduated students. This situation affects, in addition, the image of the School and its academic personnel.This research considered the student desertion to be an object of study in the level of license degree, for the breach with the TFG (Graduation final proyect), in spite of having other requirements to elaborate it. The information of this work was obtained of the students who are dealing with the courses of license degree of the School of Bibliotecology, of the National University during the period 1996-2006, which did not manage to conclude the studies plan and for that reason, they remain undergraduated from the career by a long period.